The importance of agriculture industry in rural area for economic development / Siti Fairus Sepeai - Sepeai, Siti Fairus (2012)
The aim of this study was to examine the importance of agriculture industry in rural area for economic development. There are three factors that have been studied, which are: job opportunities, generate income and poverty reduction. In collecting data, the researcher used primary data. The questionnaires had been used in order to get feedback from the workers who involved in agriculture industry. Researcher had distributed 100 questionnaires to all workers who involved in agriculture industry in area Tanah Merah. The data collected was tested on its frequency analysis. Further analysis had been done by using reliability analysis. Correlation was used to test the hypotheses in this study as well as regression analysis. The findings of this study show that all independent variables which are job opportunities, generate income and poverty reduction have relationship with the importance of agriculture industry. All of three factors which are job opportunities, generate income and poverty reduction positively influence the importance of agriculture industry in rural area. From the result obtained in this study, researcher suggests some recommendations that can help agriculture industry to improve their industry and at the same time increase the workers awareness